Research on seeding agents to effect the sugar crystallization - Popa, Dorin; Sarca, Gheorghe (Acta Agraria Debreceniensis, 2010)
The quality of sugar is the decisive factor in ensuring the sugar commercializing through the conservation of old markets andexpansion towards new markets. The sugar quality is also the key element which determines the price maintenance in according with theexpenditures performed or even the diminution of the price as a consequence of the quality lessening.